1999
DOI: 10.1034/j.1399-302x.1999.140410.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oral Actinomyces species using DNA probes

Abstract: Oral Actinomyces comprise a major segment of both the supra- and subgingival microbiota; however, little is known about the distribution of individual species in different sites or clinical conditions. The purpose of the present investigation was to develop DNA probes for suggested species and genotypes of oral Actinomyces. Whole genomic DNA probes to 12 human oral species and/or serotypes were labeled with digoxigenin and used to seek cross-reactions among the taxa using the checkerboard DNA-DNA hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Identification of Actinomyces species has been hampered by problems with traditional biochemical methods of characterization. Although some studies have applied DNA hybridization methods (120, 189–191), these are not readily applicable and reproducible from one lab to another. The partial characterization of the 16S rRNA gene (192) has facilitated the development of probes suited to widespread application (193–195).…”
Section: Flora In Root‐filled Canalsmentioning
confidence: 99%
“…Identification of Actinomyces species has been hampered by problems with traditional biochemical methods of characterization. Although some studies have applied DNA hybridization methods (120, 189–191), these are not readily applicable and reproducible from one lab to another. The partial characterization of the 16S rRNA gene (192) has facilitated the development of probes suited to widespread application (193–195).…”
Section: Flora In Root‐filled Canalsmentioning
confidence: 99%
“…A. odontolyticus has been shown to be one of the predominant Actinomyces species in developing biofilms on tooth surfaces in subjects of all ages, and the proportions found were not related to periodontal disease status (31). In a study characterizing 195 fresh Actinomyces isolates collected from supra-and subgingival plaque samples of five adults with chronic periodontitis, A. oris (formerly A. viscosus serotype II) was the isolate most commonly identified, followed by A. gerencseriae, A. naeslundii, A. georgiae, and A. israelii; A. meyeri was not found (32). In general, members of the genus Actinomyces are not considered to play a pathogenic role in periodontitis.…”
Section: Oral Cavitymentioning
confidence: 99%
“…Previous studies have also reported on the intra- and inter-species diversities of A. naeslundii and A. oris , as A. naeslundii genospecies 1 and 2 using DNA fingerprinting [11], ribotyping [5], [12], amplified 16S ribosomal DNA restriction analysis (ARDRA) [4], [13], DNA probes [14], sequence analysis of fimA genes [9] and REP-PCR amplicons analysis [10]. All these studies have demonstrated extensive heterogeneity within each taxon.…”
Section: Introductionmentioning
confidence: 99%